Acute effects of high-intensity interval, resistance or combined exercise protocols on testosterone – cortisol responses in inactive overweight individuals (2018)
The purpose of this study was to compare the hormonal responses to one session of high-intensity interval training (HIIT, 4 × 4 min intervals at 85–95% maximum heart rate [HRmax], interspersed with 4 min of recovery at 75–85% HRmax), resistance training (RT at 50–70% of one repetition maximum 12–15 repetitions per set with 60s of recovery) or both (HIIT+RT) exercise protocol in a cohort of physical inactivity, overweight adults (age 18–30 years old). Randomized, parallel-group clinical trial among fifty-one men (23.6 ± 3.5 yr; 83.5 ± 7.8 kg; 28.0 ± 1.9 kg/m2), physical inactivity (i.e., and lt;150 min of moderate-intensity exercise per week for and gt;6 months), with abdominal obesity (waist circumference ?90 cm) or body mass index ?25 and ?30 kg/m 2 were randomized to the following 4 groups: high-intensity interval training (HIIT, n = 14), resistance training (RT, n = 12), combined high-intensity interval and resistance training (HIIT+RT, n = 13), or non-exercising control (CON, n = 12). Cortisol, total- and free-testosterone and total-testosterone/cortisol-ratio (T/C) assessments (all in serum) were determined before (pre) and 1-min post-exercise for each protocol session. Decreases in cortisol levels were ?57.08 (95%CI, ?75.58 to ?38.58; P = 0.001; ? 2 = 0.61) and ? 37.65 (95%CI, ?54.36 to ?20.93; P = 0.001; ? 2 = 0.51) in the HIIT and control group, respectively. Increases in T/C ratio were 0.022 (95%CI, 0.012 to 0.031; P = 0.001; ? 2 = 0.49) and 0.015 (95%CI, 0.004 to 0.025; P = 0.007; ? 2 = 0.29) in the HIIT and control group, respectively. In per-protocol analyses revealed a significant change in cortisol levels [interaction effect F( 7.777 ), ? 2 = 0.33] and T/C ratio [interaction effect F( 5.298 ), ? 2 = 0.25] between groups over time. Additionally, we showed that in both the intention-to-treat (ITT) and per protocol analyses, HIIT+RT did not change serum cortisol, total or free testosterone. The present data indicate a HIIT reduced cortisol and increased total-testosterone/cortisol-ratio levels significantly in physically inactive adults. Further study is required to determine the biological importance of these changes in hormonal responses in overweight men. © 2018 Elsevier Inc.